2017
DOI: 10.1364/oe.25.018537
|View full text |Cite
|
Sign up to set email alerts
|

Organic membrane photonic integrated circuits (OMPICs)

Abstract: We propose the concept of organic membrane photonic integrated circuits (OMPICs), which incorporate various functions needed for optical signal processing into a flexible organic membrane. We describe the structure of several devices used within the proposed OMPICs (e.g., transmission lines, I/O couplers, phase shifters, photodetectors, modulators), and theoretically investigate their characteristics. We then present a method of fabricating the photonic devices monolithically in an organic membrane and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This vertical integration concept can be further extended to a wide range of electronics, since the entire membrane-based photonic layer is completely independent from the carrier. An interesting development is the integration of an InP photonic membrane on an organic substrate [143], developed at Tokyo Tech. The feasibility study in [143] has shown that the InP membranes can be bent to a very short radius (up to 100 µm for a 200 nm thick membranes).…”
Section: Heterogeneous Integration On Electronicsmentioning
confidence: 99%
“…This vertical integration concept can be further extended to a wide range of electronics, since the entire membrane-based photonic layer is completely independent from the carrier. An interesting development is the integration of an InP photonic membrane on an organic substrate [143], developed at Tokyo Tech. The feasibility study in [143] has shown that the InP membranes can be bent to a very short radius (up to 100 µm for a 200 nm thick membranes).…”
Section: Heterogeneous Integration On Electronicsmentioning
confidence: 99%
“…Near-infrared (NIR) lasers are widely employed throughout optical communications, [1][2][3] integrated photonic circuits, [4][5][6] and biomedical diagnostics. [7][8][9] Ever-increasing system accuracy and integration require high temperature stability of the lasing threshold and emission photon energy.…”
Section: Introductionmentioning
confidence: 99%
“…Since their emergence more than 20 years ago [42,43] the ease of their manufacture and relatively low cost enabled their use in many optoelectronic applications such as lasers sources [41], light-emitting diodes (LEDs) [44,45], photodetectors [46], and solar cells [47,48]. Moreover, similarly to epitaxially grown QDs, they were utilized in integrated-photonic circuits [49][50][51][52], lab-on-chip platforms [53], optical interconnects [54][55][56], or advanced medical devices [57][58][59][60]. Moreover, colloidal QDs were realized for different material systems from the periodic table groups II-VI, III-V, or IV-VI.…”
Section: Introductionmentioning
confidence: 99%